Penanganan Covid-19 dalam Semangat Diakonia Gereja Keuskupan Ruteng - Max Regus; Marianus Mantovanny Tapung (LPMP Imperium, 2020)
Covid-19 is a non-natural disaster that is not only related to health issues but also has links to economic, psycho-social, and even social-political problems. As an institution that takes care of the safety of body and soul, the Catholic Church of the Ruteng Archdiocese, as one of the socio-religious institutions, responds to this problem by directly forming the Covid-19 solidarity movement, which is later institutionalized as the Gugus Tanggap Cluster Covid-19 Church Ruteng Diocese and Covid-19. As academics by involving in this task, authors consider the formation of an “ad hoc” institution as part of the attention and responsibility of the Local (religious) Church in dealing with the social problems of the community/community, both in local, national and global contexts. This action is the contextualization of the praxis of service (deaconess) of the Church for the lives of people, more specifically in the field of health. In carrying out its governance, the Covid-19 Group applies the stages of methods and implementation consisting of the activities of Coordination, Action (promotion, prevention, education, social assistance), Evaluation, and Follow-up Plans. The real impact of the work of the Covid-19 Cluster, the people/communities returning to the enthusiasm and have optimism in running life, while; hoping that the Covid-19 pandemic will soon pass its life. Keywords: Covid-19, Religion, Church, Solidarity, Command Post